Electron Transfer between Ruthenium (II)-(trisbipyridine) Ru and Cobalt(III)-(polypyridyl) Co at , , and Acetone Solvents - Hadi Mejbel (University of Thi-Qar Journal of Science, 2019)
A theoretical calculations of electron transfer at metals interfaces are performed to study the electrontransfer for Ru - Co system at ,, ,and acetone solvents. This study is basedon the assumption that metals have a continuum of donor's and acceptor's states .The rate of electrontransfer,the reorganization energy ,the enthalpy , the effective free energy, and coupling coefficient of matrixelements ,V, were calculated for the donor Ru and acceptor in variety of solvents. The resultsshow that the electron transfer in Ru system at solvents is fast and efficient. Our calculations showgood agreement with the experimentally observed results for metals complex.